Comparative wood anatomy of Rubroshorea leprosula across multiple populations in Sumatra Island, Indonesia - AINUN FADILAH; FIFI GUS DWIYANTI; TRIADIATI TRIADIATI; AGUS HIKMAT; LINA KARLINASARI; ISKANDAR ZULKARNAEN SIREGAR (Society for Indonesian Biodiversity, 2026)
Abstract. Fadilah A, Dwiyanti FG, Triadiati, Hikmat A, Karlinasari L, Siregar IZ. 2026. Comparative wood anatomy of Rubroshorea leprosula across multiple populations in Sumatra Island, Indonesia. Biodiversitas 27 (2): d270204. https://doi.org/10.13057/biodiv/d270204. Red meranti wood (Rubroshorea leprosula) is classified in strength classes II-IV and durability classes III-IV, making it suitable for light and heavy construction due to its high wood quality. This has led to widespread exploitation, illegal logging, and illicit trade, particularly from natural forests. Current conservation strategies lack adequate scientific support, particularly in species and origin identification, which are crucial for wood tracking. Wood anatomy is a simple, rapid, and reliable method for identifying wood species. Therefore, this study aimed to evaluate the wood anatomy of R. leprosula by examining visual, macroscopic, and microscopic structures to identify key characteristics that differentiate between populations. Visual characteristics were assessed based on wood color, pattern, texture, gloss, and grain orientation. Macroscopic observations were made of growth rings, vessels, intercellular canals, axial parenchyma, and ray parenchyma. Microscopic analysis was performed using a light microscope to observe cellular structures qualitatively and quantitatively. Samples were collected from five populations in Sumatra, Indonesia. Fifty wood samples (ten per population) were analyzed. Data were statistically analyzed using One-Way ANOVA and post-hoc tests to identify significant differences between populations. The results showed that evaluation of the microscopic structure successfully identified key characteristics, particularly variations in vessel diameter, that consistently differentiated among populations, with significant differences (p-value = 0.00000545) ranging from 105.2-158.7µm, most notably between samples from Bukit Tigapuluh National Park and Harapan Rainforest (p-value<0.025). This anatomical variation, potentially related to hydraulic conductivity and ecological adaptation, indicates population differentiation. This study contributes to forest biology by linking anatomical traits to adaptive functions and traceability, which are essential for the sustainable management of tropical timber resources.